2017
DOI: 10.1038/ejcn.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

Association between coffee or tea drinking and Barrett’s esophagus or esophagitis: an Italian study

Abstract: BACKGROUND/OBJECTIVES: Only a few papers have treated of the relationship between Barrett's esophagus (BE) or erosive esophagitis (E) and coffee or tea intake. We evaluated the role of these beverages in BE and E occurrence. SUBJECTS/METHODS: Patients with BE (339), E (462) and controls (619) were recruited. Data on coffee and tea and other individual characteristics were collected using a structured questionnaire. RESULTS: BE risk was higher in former coffee drinkers, irrespective of levels of exposure (cup p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…However, some recent studies reported that frequent tea drinking might association with the risk of GERD. Chang et al [12] conducted a cross-sectional study to evaluate the effect of regular tea drinking on asymptomatic erosive esophagitis. They found that the risk of asymptomatic erosive esophagitis was greater in those drinking tea than nondrinkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some recent studies reported that frequent tea drinking might association with the risk of GERD. Chang et al [12] conducted a cross-sectional study to evaluate the effect of regular tea drinking on asymptomatic erosive esophagitis. They found that the risk of asymptomatic erosive esophagitis was greater in those drinking tea than nondrinkers.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the risk of asymptomatic erosive esophagitis was greater in those drinking tea than nondrinkers. [13] Another study performed by Filiberti et al [12] suggested that tea consumption could be protective factor for Barrett's esophagus or esophagitis. However, this is a case–control study based on limited subjects.…”
Section: Discussionmentioning
confidence: 99%
“…No association between risk of BE and consumption of coffee or tea was found by Sajja et al[35]. An Italian study conducted by Filiberti et al[36] revealed that tea intake reduced the risk of BE and reflux esophagitis. A double-blind study performed by Pehl et al[37] compared the impact of regular and decaffeinated coffee on esophageal acidity in terms of esophageal pH measurements, and reported that the fraction of time for which esophageal pH was less than 4 was reduced in the decaffeinated coffee-consuming group potentially via a reduction in esophageal reflux.…”
Section: Discussionmentioning
confidence: 99%
“…Coffee drinking has been associated with positive health outcomes [ 44 ]. Regarding espresso coffee, despite it being reported to provide an important antioxidant capacity within the context of a common diet [ 45 , 46 ], results regarding its effects on health are varied, ranging from positive [ 47 , 48 , 49 ] to negative [ 50 , 51 , 52 ]. In general, scientific literature on espresso coffee is scarce, and further research is needed to test the impact of this beverage on human health.…”
Section: Discussionmentioning
confidence: 99%